1982
DOI: 10.1002/1097-0142(19820715)50:2<201::aid-cncr2820500205>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

A phase II evaluation of adriamycin and cis-platinum in hormone resistant prostate cancer

Abstract: Twenty‐five patients with metastatic prostate cancer were treated with a combination of Adriamycin 50 mg/m2 and cis‐platinum (CDDP) 50 mg/m2 every three weeks. Response was evaluated using radioisotope bone scan, serum acid phosphatase levels, and clinical status. Response rates of 6% bone, 21% acid phosphatase, and 24% clinical status were noted. Major toxicity was gastrointestinal (due to CDDP). Treatment was well tolerated even in patients with extensive bone metastases and prior irradiation. Using the resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1983
1983
2006
2006

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Response criteria used to assess therapeutic effectiveness in prostate cancer are controversial (8,9). The results of our trial failed to identify significant antitumor activity for esorubicin in hormone resistant prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Response criteria used to assess therapeutic effectiveness in prostate cancer are controversial (8,9). The results of our trial failed to identify significant antitumor activity for esorubicin in hormone resistant prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in a Phase II trial of doxorubicin and cisplatin, significant improvements were demonstrated in prostatic acid phosphatase in 21% of patients, and clinical improvement was observed in 24% of patients. 18 Additional trials have combined cisplatin with doxorubicin plus 5-flourouracil, 16 with strontium-89 ( 89 Sr), 22,30 with etoposide plus pirarubicin, 32 with mitoxantrone, 33 with estramustine plus etoposide, 19 and with calcitriol plus dexamethasone. 90 Some regimens have been targeted specifically against small cell carcinoma, with cisplatin and etoposide as the core elements of the regimen.…”
Section: Multiagent Regimens That Include Cisplatin and Carboplatinmentioning
confidence: 99%
“…15 Although earlier studies suggested a lack of activity, more recent studies using palliation and PSA endpoints have suggested a greater degree of clinical benefit. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] In addition, several recent clinical trials have combined carboplatin with taxanes and demonstrated promising results. [34][35][36] Finally, a new platinum analogue, satraplatin, has demonstrated intriguing activity in HRPC and is being tested in a large randomized study in the second-line chemotherapy setting.…”
mentioning
confidence: 99%
“…Since ethical considerations prohibit study of a series of untreated controls who failed with hormone therapy, concern about the use of stable as a category is afi issue that cannot be completely resolved, but nevertheless is an important entity in evaluating therapies for, and management of, the patient with advanced disease.' ', [31][32][33][34] It has been pointed out that total response rates of 30% or better have been reported by the NPCP for a number of agents studied in their clinical trials, in which only 2% to 6% of this response rate was made up of objective partial responses.32 Such an argument implies that only partial (or complete) responses have any real meaning or value, supposedly for indicating the efficacy of treatment, which in turn should reflect an improvement in the patient's well-being. The alternate or counter argument, of course, is that stable does not reflect treatment efficacy and/or patient well-being.…”
Section: Age At Entry (Years)mentioning
confidence: 99%